Development of LKPD Based on a Realistic Mathematics Education Approach to Improve Higher-Level Thinking Abilities (HOTS) - Tawa, Maria Goreti; Maria Carmelita Tali Wangge; Wilibaldus Bhoke; Melkior Wewe (Desimal: Jurnal Matematika, 2026)
This study addresses the persistent challenge of fostering Higher Order Thinking Skills (HOTS) in mathematics learning, particularly in social arithmetic topics, where conventional instructional materials often fail to promote analytical and evaluative thinking. This research aims to develop and validate a student worksheet (LKPD) grounded in the Realistic Mathematics Education (RME) approach, designed to systematically support the development of HOTS through contextual problem-solving and guided reinvention processes. Employing a Research and Development (R&D) design with the ADDIE model, the study involved iterative stages of analysis, design, development, implementation, and evaluation, incorporating both qualitative feedback and quantitative assessment. The product was validated by subject matter and media experts, yielding high validity scores (3.78 and 3.54, respectively), indicating strong alignment with pedagogical and content standards. Field implementation with seventh-grade students demonstrated high practicality, reflected in a positive response rate of 93.76%. More importantly, the integration of contextual mathematical tasks facilitated students’ engagement in higher-order cognitive processes, including analysis, evaluation, and problem-solving within real-life scenarios. These findings suggest that the developed LKPD not only meets feasibility criteria but also functions as an effective pedagogical design that bridges theoretical principles of RME with HOTS-oriented instruction. This study contributes to mathematics education by offering an empirically validated instructional design that enhances cognitive engagement and supports meaningful learning in secondary education contexts.